Fluoride Contamination and Water Quality Status - Hayat, Fauzul; Mukhlasin, Mukhlasin; Kurniatillah, Nia (KnE Social Sciences, 2023)
River fluoride contamination is one of public health problems. This study aims to determine the water quality status and fluoride contamination analyses of Cirarab River, Banten-Indonesia. Water sampling was conducted along the Cirarab River from up to downstream at eight (8) stations from February to June 2016. Water fluoride was analyzed using SPADNS method and STORET method for determining water quality status. Results show that the average water fluoride ranges from 2-2.24 mg/L. The maximum fluoride concentration obtained in station 4 (3 mg/L) was recorded in April 2016. Based on the World Health Organization’s (WHO) maximum acceptable fluoride levels of 1.50 mg/l, the overall results show that the water quality status of the Cirarab River was heavily polluted. In some situations, there was a need for continuous monitoring and warning drinking water management resources to minimize the long term health effects on communities consuming, and also the policies that are necessary to achieve sustainable water quality. Keywords: fluoride, Cirarab Rivers, water quality